HO-1 and Heme: G-Quadruplex Interaction Choreograph DNA Damage Responses and Cancer Growth - Giacomo Canesin; Anindhita Meena Muralidharan; Kenneth D. Swanson; Barbara Wegiel (Cells, 2021)
Many anti-cancer therapeutics lead to the release of danger associated pattern molecules (DAMPs) as the result of killing large numbers of both normal and transformed cells as well as lysis of red blood cells (RBC) (hemolysis). Labile heme originating from hemolysis acts as a DAMP while its breakdown products exert varying immunomodulatory effects. Labile heme is scavenged by hemopexin (Hx) and processed by heme oxygenase-1 (HO-1, Hmox1), resulting in its removal and the generation of biliverdin/bilirubin, carbon monoxide (CO) and iron. We recently demonstrated that labile heme accumulates in cancer cell nuclei in the tumor parenchyma of Hx knockout mice and contributes to the malignant phenotype of prostate cancer (PCa) cells and increased metastases. Additionally, this work identified Hx as a tumor suppressor gene. Direct interaction of heme with DNA G-quadruplexes (G4) leads to altered gene expression in cancer cells that regulate transcription, recombination and replication. Here, we provide new data supporting the nuclear role of HO-1 and heme in modulating DNA damage response, G4 stability and cancer growth. Finally, we discuss an alternative role of labile heme as a nuclear danger signal (NDS) that regulates gene expression and nuclear HO-1 regulated DNA damage responses stimulated by its interaction with G4.